Groundwater flow and heterogeneous discharge into a seepage lake: Combined use of physical methods and hydrochemical tracers. Issue 11 (30th November 2016) - Kazmierczak, J.; Müller, S.; Nilsson, B.; Postma, D.; Czekaj, J.; Sebok, E.; Jessen, S.; Karan, S.; Stenvig Jensen, C.; Edelvang, K.; Engesgaard, P.
Abstract: Groundwater discharge into a seepage lake was investigated by combining flux measurements, hydrochemical tracers, geological information, and a telescopic modeling approach using first two‐dimensional (2‐D) regional then 2‐D local flow and flow path models. Discharge measurements and hydrochemical tracers supplement each other. Discharge measurements yield flux estimates but rarely provide information about the origin and flow path of the water. Hydrochemical tracers may reveal the origin and flow path of the water but rarely provide any information about the flux. While aquifer interacting with the lake remained under seemingly steady state conditions across seasons, a high spatial and temporal heterogeneity in the discharge to the lake was observed. The results showed that part of the groundwater flowing from the west passes beneath the lake and discharges at the eastern shore, where groundwater springs and high discharge zones (HDZs) are observed at the lake bottom and at seepage faces adjacent to the lake. In the 2‐D cross section, surface runoff from the seepage faces delivers 64% of the total groundwater inputs to the lake, and a 2 m wide offshore HDZ delivers 13%. Presence of HDZs may control nutrient fluxes to the lake. Key Points: Seepage lake interacting with aquifer under seemingly steady state conditions shows high spatial and temporal heterogeneity in discharge Groundwater discharge to the lake is focused at the adjacent wetlands and in high discharge zone occupying ∼1% of the lake bottom Integration of hydrogeological, geological, and hydrochemical data is needed to reliably conceptualize the groundwater‐lake interactions